Serological and Hematological Study of Toxoplasmosis in Blood of Newly Born Babies - Assit, Khairy A. Dawood; Talib, Ruaa A.; Falah, Hasanain (Medical Science Journal for Advance Research, 2021)
Serological identification and blood pictures were done for specific IgM and IgG.10% of cases were positive IgM of Toxoplasmosis because have 10 IU/ml (mean) in comparison with control group were 0.11 IU/ml (mean). On other hand 20% of diagnosed cases were positive IgG of Toxoplasmosis because have 11 IU/ml .Two cases were followed for their history one from group IgM and other IgG , first one suffered from three abortion and now have five child three of them healthy while two have congenital defects. Second case (IgG positive ) have four abortion and now have three child , two healthy and one have congenital defect. Blood picture reveal 40% suffered from Normocytic anemia , these cases classified to three groups , first Toxoplasma group 30% (positive in ELISA test). Second group (Unknown causes), these cases not only normocytic anemia also have high total leukocytes 17 x10 (mean) and high MCV (103 ft). Third group have low MCV 78ft.